1994
DOI: 10.1051/parasite/199401s1057
|View full text |Cite
|
Sign up to set email alerts
|

Cuticlin genes of nematodes

Abstract: CUTICLIN GENES OF NEMATODESLEWIS E.*, SEBASTIANO M.*, NOLA M.*, ZEI F.*, LASSANDRO F.*, RISTORATORE F.,* CERMOLA M.*, FAVRE R.* AND BAZZICALUPO P.* KEYWORDS : parasitic nematodes, cuticle, cuticlin. dityrosine. cross-linking. SUMMARYTwo genes coding for cuticlin components of Caenorhabditis elegans have been cloned and their structure is described. Recombinant pro teins have been produced in E. coli and antibodies raised against them. Nucleic acid and specific antibodies are being used to isolate the homologue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Cuticlin is another structural component of the cuticle. It is abundant in the outermost cortical layers and hypothesized to be enzymatically polymerized to constrict the seam cell-derived cuticle and thereby form the distinctive cuticular alae in C. elegans [25] , [26] , [29] . In this study, we identified 158 gene copies encoding cuticle collagens, and each expressed product contained a nematode cuticle collagen N-terminal domain and/or collagen triple helix repeats (n = 20) ( Figure 4 ; Table S24 ).…”
Section: Resultsmentioning
confidence: 99%
“…Cuticlin is another structural component of the cuticle. It is abundant in the outermost cortical layers and hypothesized to be enzymatically polymerized to constrict the seam cell-derived cuticle and thereby form the distinctive cuticular alae in C. elegans [25] , [26] , [29] . In this study, we identified 158 gene copies encoding cuticle collagens, and each expressed product contained a nematode cuticle collagen N-terminal domain and/or collagen triple helix repeats (n = 20) ( Figure 4 ; Table S24 ).…”
Section: Resultsmentioning
confidence: 99%
“…One of the main constitutive and highly cross-linked and insoluble proteins is cuticlin-1, which is a potent inducer of antibody production [65] and probably it has to be continuously renewed. It is found in pseudocolemic fluid and its genes increase its expression before each moult [66]. Cuticular collagen 12 and 13 are the essential components of the Ascaris envelope [13].…”
Section: Structural Antigensmentioning
confidence: 99%
“…However, the majority of ZPD proteins in C. elegans are simply annotated as CUT-like or CUTL proteins and little is known about their biology. Not surprisingly, even less is known about ZPD protein biology in nematodes beyond C. elegans , though it has been suggested that study of cuticlin proteins may aid efforts to pharmacologically attack the cuticles of nematodes that parasitize humans, livestock, and crops ( Lewis et al. 1994 ; Ondrovics et al.…”
Section: Introductionmentioning
confidence: 99%